Governing Enclosure: The Role of Governance in Producing Gated Communities and Guarded Neighborhoods in Malaysia - Tedong, Peter Aning; Grant, J.L.; Wan Abd Aziz, Wan Nor Azriyati (Blackwell Publishing, 2015)
Enclosed residential areas are proliferating in Malaysian cities, in common with many other parts of the world. The production of gated communities and guarded neighborhoods in Malaysia reveals the active role of the state in creating conditions that support enclosure and securitization of space. This article examines the role of governance in producing residential enclaves that reinforce segregation and fragment urban landscapes. Based on a study of gated communities in Malaysia, we argue that governments, corporations and citizen groups collaborate within a complex governance system that (re)produces enclosure. Neoliberal market principles fuse with ethnic politics, cultural predilections and economic imperatives to generate a socially and spatially fragmented urban landscape where security concerns dominate and where citizens culturally, physically and symbolically segregate themselves from others.